Meningkatkan Minat dan Hasil Belajar Peserta Didik melalui Penerapan Model Pembelajaran Problem Solving Laboratory (PSL) pada Mata Pelajaran Fisika - Zulaifah, Umi (FKIP Unirow Tuban, 2023)
This Classroom Action Research was conducted to determine the increase in interest and learning outcomes in Physics for class Data collection methods use observation, tests and practicum methods. Data analysis uses data reduction, data presentation and drawing conclusions. In cycle 1 to cycle 2, the percentage of students whose interest was sometimes in all indicators continued to decline, namely the indicator of attention (35.14% - 27.02% - 2.70%), the indicator of interest (24.32% - 21.6%, - 0%), happiness indicator (29.72% -24.3%,- 0%). Student learning outcomes also increased after the action was taken. The percentage of students who have not completed has decreased from the initial condition (72.97% - 51.3% - 13.51%) for knowledge scores, (51.35% - 32.43% - 10.81%) for skills scores, a decrease in the predicate moderately (70.27% - 48.65% -10.81%) for affective value. The percentage of students who have completed has increased from cycle 1 to cycle 2 (27.03% - 48.6% - 86.49%) for knowledge scores, (48.65% - 67.57% - 89.19%) for skill scores and an increase in good and very good scores (29.73% - 51.35% - 89.19%) for affective scores. Thus the hypothesis of this research is proven. Actions are said to be successful if at least students have an interest percentage greater than 80% for all indicators. And the average score of students at the end of the cycle, the percentage who obtained a score above the KKM had reached greater than 80% for all knowledge, skills and affective scores. So, this PTK was declared to have succeeded in increasing interest and learning outcomes.